Third generation gold nanoplatform optimized for radiation therapy - Kumar, Rajiv; Korideck, Houari; Ngwa, Wilfred; Berbeco, Ross I.; Makrigiorgos, G. Mike; Sridhar, Srinivas (Translational Cancer Research; Vol 2, No 4 (August 26, 2013): Translational Cancer Research (Nanotechnology in Radiation Research), 2013)
We report the design and fabrication of third generation ultrasmall PEGylated gold nanoparticles based platform (AuRadTM) optimized for applications in radiation therapy. The AuRadTM nanoplatform has the following key features: (I) surface coating of hetero-bifunctional-PEG with amine, carboxyl, methoxy functional groups, which make this a versatile nanoplatform to conjugate various moieties like fluorophores, peptides, drugs, radiolabels; (II) size that is optimized for longer circulation, higher tumor uptake and modulated clearance; (III) high radiation enhancement. We have synthesized ultrasmall 2-3 nm gold nanoparticles, followed by attachment of hetero-bifunctional PEG and further conjugation of fluorophore AlexaFlour 647 for optical imaging, with a stability of more than 6 months. Confocal bioimaging with HeLa cells showed robust uptake of biocompatible nanoparticles in cells. Irradiation experiments X-rays showed greater than 2.8-fold cell kill enhancement as demonstrated by clonogenic survival assays. The results indicate that AuRad nanoplatform can act as potential theranostic agent in radiation therapy.